Stress development in thermal barrier coatings with morphology-controlled thermally grown oxide. Issue 16 (November 2019) - Chai, Yijun; Yang, Xiongwei; Li, Yueming; Ogawa, Kazuhiro
Abstract: Formation of thermally grown oxide (TGO) on the interface between top coat (TC) and bond coat (BC) is critical for thermal barrier coating system (TBCs) failure during long-term exposure. Because the oxidation is inevitable, alternative control of the TGO morphology may provide a new perspective in improving the anti-spalling behavior of TBCs. In this work, a TGO morphology with "root-like" oxides penetrating into the BC is studied, and effects of the "root-like" oxides on the stress development are thoroughly investigated through combining a diffusion-oxidation reaction model and a creep-plastic constitutive model. Results show that the maximum tensile stress now locates inside the BC rather than on the interface, implying that the morphology could alter propagation direction of cracks and thus enhance the interfacial delamination resistance of TBCs. Controlling of the TGO morphology offers some new insights in increasing the TBCs bond strength, and may have great potentials in the thermal-engineering industry.